Early Childhood Social Skills Development Through Hyflex Learning (Flexible Hybrid) - Hikmah Munawaroh; Sri Kuswantono; Sofia Hartati; Yudrik Jahja; Yasmin Faradiba (Jurnal Indonesia Sosial Teknologi, 2023)
Social skills need to be familiarized from an early age because children will carry these habits into adulthood. This study aims to find a learning model to develop social-emotional skills through hyflex learning. Face-to-face, hybrid (blended) learning should give early childhood flexibility to learn. HyFlex learning gives students choices about how they attend class through face-to-face, synchronous, and asynchronous technology. An alternative to achieving this goal is to develop a hybrid learning model that can be used to teach these early childhood social skills. The HyFlex Learning Model is a new form of learning in early childhood education. The selection of the model is based on the initial needs analysis in DKI Jakarta, where most ECCE educators need a learning model to develop children's social performance that can be applied during the Face-to-Face Meeting period to learning activities in PAUD which is limited in nature can be done optimally. The method used is research and development (Research and Development) which includes activities (1) researching and collecting information, including reading literature, observing classes, and preparing reports on development needs, (2) planning prototype components to be developed, (3) developing initial prototypes; (4) conduct limited trials, (5) revise, (6) test results, (7) revise product designs, (8) conduct field trials operationally, (9) make final revisions to the media, and (10) disseminate to various parties. The results of the model trial conducted obtained an assessment percentage of 83% with a decent assessment category, so this model is suitable for teaching Social Skills.